2006
DOI: 10.1016/j.cellsig.2005.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface targeting of α2-adrenergic receptors — Inhibition by a transport deficient mutant through dimerization

Abstract: We previously demonstrated that the α 2B -adrenergic receptor mutant, in which the F(x) 6 IL motif in the membrane-proximal carboxyl terminus were mutated to alanines (α 2B -ARm), is deficient in export from the endoplasmic reticulum (ER). In this report, we determined if α 2B -ARm could modulate transport from the ER to the cell surface and signaling of its wild-type counterpart. Transient expression of α 2B -ARm in HEK293T cells markedly inhibited cell-surface expression of wild-type α 2B -AR, as measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 46 publications
(99 reference statements)
2
41
0
Order By: Relevance
“…We have demonstrated that the cell surface expression of AT1R is regulated by Ras-like small GTPases, such as Rab1, Rab2, Rab6, Sar1, and ARF1 in HEK293 cells and cardiac myocytes (29,(43)(44)(45)(46). We have also demonstrated that AT1R exit from the ER is mediated through the COPII vesicles and controlled by the F(X) 6 LL motif in the membrane-proximal C terminus and a single Leu residue in the center of the first intracellular loop (23,24,29,47). These studies indicate that, similar to endocytosis, cell surface export of AT1R is a highly regulated process.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…We have demonstrated that the cell surface expression of AT1R is regulated by Ras-like small GTPases, such as Rab1, Rab2, Rab6, Sar1, and ARF1 in HEK293 cells and cardiac myocytes (29,(43)(44)(45)(46). We have also demonstrated that AT1R exit from the ER is mediated through the COPII vesicles and controlled by the F(X) 6 LL motif in the membrane-proximal C terminus and a single Leu residue in the center of the first intracellular loop (23,24,29,47). These studies indicate that, similar to endocytosis, cell surface export of AT1R is a highly regulated process.…”
mentioning
confidence: 70%
“…Mutagenesis studies have also identified a number of highly conserved motifs in the membrane-proximal C termini essential for GPCR export from the ER, such as the E(x) 3 LL, FN(x) 2 LL(x) 3 L, and F(x) 3 F(x) 3 F motifs (22,26,27). We have recently identified the F(x) 6 LL motif in the 8 th ␣-helix, which modulates export of ␣ 2B -AR, ␤ 2 -AR, ␣ 1B -AR, and AT1R from the ER (24,25,47). In the present study, we have demonstrated that the membrane-distal C terminus is also absolutely required for AT2R anterograde transport to the cell surface as the AT2R mutant lacking the C-terminal 7 residues was unable to transport to the cell surface, which is similar to the mutant lacking the entire C-terminal 42 residues.…”
Section: Discussionmentioning
confidence: 99%
“…NG108-15 neuroblastoma-glioma cells were cultured in DMEM containing 10% fetal bovine serum, 100 units/ml of penicillin, 100 g/ml of streptomycin, 100 M hypoxanthine, 0.4 M aminopterin, and 16 M thymidine as described previously (40). HL-1 cardiac myocytes were plated onto fibronectin-gelatin-coated plates or coverslips and cultured in Claycomb medium supplemented with 10% fetal bovine serum, 100 units/ml of penicillin, 100 g/ml of streptomycin, 0.1 mM norepinephrine, and 2 mM L-glutamine as described previously (26,41).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that export from the ER is a rate-limiting step for maturation of the δ-opioid receptor [8], and accumulation of misfolded receptors in the ER is associated with the pathogenesis of human disease [9,10]. Second, GPCR export from the ER is directed by highly conserved motifs in the membrane-proximal termini [11][12][13][14][15]. We have recently identified the F(X) 6 LL motif in the C-termini required for α 2B -adrenergic (α 2B -AR) and angiotensin II type 1 receptor (AT1R) export from the ER [14,15] and the YS motif in the N-termini essential for α 2 -AR export from the Golgi [16].…”
Section: Introductionmentioning
confidence: 99%
“…Second, GPCR export from the ER is directed by highly conserved motifs in the membrane-proximal termini [11][12][13][14][15]. We have recently identified the F(X) 6 LL motif in the C-termini required for α 2B -adrenergic (α 2B -AR) and angiotensin II type 1 receptor (AT1R) export from the ER [14,15] and the YS motif in the N-termini essential for α 2 -AR export from the Golgi [16]. Third, dimerization of GPCRs also plays an important role in proper receptor folding to achieve a confirmation competent for export, in addition to regulating ligand binding, signal transduction and internalization [17].…”
Section: Introductionmentioning
confidence: 99%